Psychometric Properties of a Cultural Adapted Version of the Assessment of Identity Development in Adolescence in Panama - González Flores, Sergio; Goth, Kirstin; Díaz-Hernandez, Ruben A. (Frontiers in Psychiatry, 2022)
The Assessment of Identity Development in Adolescence (AIDA) is a self-report instrument to detect pathological development of Identity. In Panamá, psychometric instruments for assessment of psychopathology in adolescence are lacking. Our aim was to develop a valid and reliable version of the AIDA Inventory for Panamanian Population. AIDA was adapted to Spanish considering cultural aspects of Panamanian population. Two pilot tests were performed prior to main test to assess item-total correlation at subscale, primary scale and total scale levels and internal consistency at subscale level. A mixed sample of students and PD patients (N = 315) completed the AIDA inventory, the “Strength and Difficulties Questionnaire” and “Defense Style Questionnaire−40.” AIDA was retested in a sub sample from school population (n = 98). The Structured Clinical Interview for Axis II Disorders was used for diagnosis of personality disorders in the patient sample (n = 25). Psychometric properties were tested to assess internal consistency, reliability, factorial validity, convergent validity, and criterion validity. AIDA Panama showed excellent internal consistency for the total scale Identity Diffusion with Cronbach's α:0.94 and a retest reliability of 0.84. A Bifactorial CFA was modeled to assess the dimensionality of the inventory. The proportion between OmegaH and Omega at total scales 96% of the variance is explained by a general factor. Furthermore, the Explained Common Variance for the General Factor is 73% supporting unidimensionality. In line with theory, AIDA total scale showed a high positive correlation (r = 0.67) with Total Difficulties scale and high positive correlation (r = 0.71) with Immature Defense scale. The AIDA total score differed highly significant (p = 0.000) between the patient sample and the students with a large effect size (d = 1.02). Conclusion The adaptation and validation of AIDA for Panamanian adolescent population was successful with good psychometric properties and significant correlations with related psychopathological constructs. AIDA showed high clinical validity by providing a valid discrimination between the school sample and a diagnosed PD sample, in line with the assumption that impaired identity functioning is at the core of personality disorders, especially in adolescence.